Enhanced Expression and Bioactivity Assessment of Recombinant SUMO-Protease-1 in E. coli BL21 (DE3) via Cleavage of His6-SMT3-SDF-1 Fusion Protein - Farzad Sadri; Hossain Safarpour; Zahra Ansari; Yazdan Ebrahimpour; Mohammad Feriedouni (Interdisciplinary Perspectives on Infectious Diseases)
Background. The SUMO fusion system is advantageous in improving the solubility and correct folding of proteins that are difficult to produce. SUMO-protease-1 (Ulp1) is a key enzyme in this system, and its proper expression and purification in Escherichia coli BL21 (DE3) are critical to its efficiency. Objective. To optimize Ulp1 expression and purification using His6-SUMO-SDF-1 as a model, aiming to improve efficiency across similar fusion proteins. Methods. We provided a codon-optimized Ulp1 gene into the pET28a vector. Essential culture factors, including IPTG concentration, incubation length of time, and temperature, were precisely adjusted. Ulp1 was purified using Ni-NTA affinity chromatography. A cleavage activity assay of recombinant Ulp1 is carried out using the His6-SUMO-SDF-1 fusion protein to demonstrate how well the optimized settings work. Furthermore, the activity of recombinant SDF-1 was evaluated using the scratch wound healing assay. Results. Ulp1 expression was optimized in E. coli using the pET28a vector, with optimum conditions including 0.1 mM IPTG, 28°C incubation temperature, and an overnight period of time. Recombinant Ulp1 was purified using Ni-NTA affinity chromatography, resulting in high purity. Enzymatic activity was shown by the effective cleavage of the His6-SUMO-SDF-1 fusion protein. In the scratch wound-healing assay, recombinant SDF-1 increased cell migration following cleavage, confirming that biological activity was retained. These findings illustrate Ulp1’s efficient synthesis and effectiveness for prospective applications in biology. Conclusion. This study successfully showed the expression and purification of the recombinant Ulp1 enzyme, showing the most suitable growing conditions for productive protein production. Ulp1’s functionality was validated by its specific cleavage of the His6-SUMO-SDF-1 fusion protein, as well as the fragmented SDF-1 purified and its biological activity in promoting cell migration. These findings highlight Ulp1’s potential in protein processing as well as its application in biotechnological and biological research.